A Rare Presentation of Haemoglobin D-thalassemia - Mohanvir Kaur; Bodal VK; Sibia RPS; Gupta D; Murarka S (GMC Patiala Journal of Research and Medical Education, 2018)
Lukens JN. The Abnormal Hemoglobins: General Principles. In. Lee GR, Foerster J, Lukens J, Paraskevas F, Greer JP, Rodgers GM, editors. Wintrobe's Clinical Hematology. Tenth ed. Baltimore: Lippincott Williams & Wilkins; 1998: 1329-45. Itano H. A third abnormal hemoglobin associated with hereditary hemolyticanemia. Proc Nat Acad Sci USA 1951; 37:775-7. Baglioni C. Abnormal human hemoglobin. VII. Chemical studies on hemoglobin D. BiochemBiophys Acta 1962; 59:437-49. Zeng YT, Huang SZ, Zhou LD, Huang HJ, Jiao CT, Tang ZG, et al. Identification of hemoglobin D Punjab by gene mapping. Hemoglobin 1986; 10:87-90. Zeng YT, Huang SZ, Ren ZR, Li HJ. Identification of HbD-Punjab gene: application of DNA amplification in the study of abnormal hemoglobins. Am J Med Genet 1989; 44:866-9. Lane PA, Witkowska HE, Falick AM, Houston ML, Mckinna JD. Hemoglobin D Ibadan-beta zero thalassemia detection by neonatal screening and confirmation by e l e c t ro s p ray - i o n i z a t i o n m a s s spectrometry. Am J Hematol 1993; 44:158-61. Foder FH, Eng CM. Molecular exclusion of haemoglobin SD disease by prenatal diagnosis. PrenatDiagn. 1999 Jan; 19(1):58-60. Rahimi Z, Akramipour R, Korani S, Nagel 0RL. Hb D-Punjab [â121(GH4) GluGln]/âï-thalassemia [IVSII.1(G-A)] in two cases from an Iranian family: first report. Am J Hematol 2006; 81: 302-3 Anuradha N, Anuradha C.R., Raghav J. 0Haemoglobin-D A Rare Case Report. 0World Journal of Medical Sciences 2014; 010 (4): 484-487. Belhoul KM, Bakir ML, Abdulrahman M. Misdiagnosis of Hb D-Punjab/â- thalassemia is a potential pitfall in hemoglobinopathy screening programs: a c a s e re p o r t . H e m o gl o b i n . 2 0 1 3 ; 37(2):119-23.